2014
DOI: 10.1177/0192623314522109
|View full text |Cite
|
Sign up to set email alerts
|

Nontraditional Applications in Clinical Pathology

Abstract: Most published reviews of preclinical toxicological clinical pathology focus on the fundamental aspects of hematology, clinical chemistry, coagulation, and urinalysis in routine toxicology animal species, for example, rats, mice, dogs, and nonhuman primates. The objective of this continuing education course was to present and discuss contemporary examples of nonroutine applications of clinical pathology endpoints used in the drug development setting. Area experts discussed bone turnover markers of laboratory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…NAC, traditionally used as an antioxidant, modulates oxidative stress-mediated liver injury and inflammation of the small intestine [13,14]. Miniature pigs as an experimental model for humans have advantages of similar sensitivity to drugs compared with other non-rodent species and similar anatomical and physiological features [17,22,23]. Dietary supplementation with NAC increased immune cell numbers and decreased the level of TNF-α production compared with CTX treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…NAC, traditionally used as an antioxidant, modulates oxidative stress-mediated liver injury and inflammation of the small intestine [13,14]. Miniature pigs as an experimental model for humans have advantages of similar sensitivity to drugs compared with other non-rodent species and similar anatomical and physiological features [17,22,23]. Dietary supplementation with NAC increased immune cell numbers and decreased the level of TNF-α production compared with CTX treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Ossabaw minipigs on the same diet also found no difference in ALT compared to control animals, whereas AST was increased. However, in pigs, GLHD is considered a more reliable marker of acute liver damage, as compared to ALT, which is non-specific in pigs [26]. Also, in human patients with NAFLD, ALT values have not been found to correlate with the degree of histopathological changes [27].…”
Section: Discussionmentioning
confidence: 99%
“…Urinalysis in rabbits is not recommended for pivotal ocular toxicity studies since rabbit urine usually has a thick consistency due to the presence of mucus, sex gland secretions, and calcium carbonate crystals making voided samples often unsuitable for analysis. 84 In the author's experience, handling and procedures (intraocular injections, ocular examinations, and blood collections) in ocular toxicity studies of rabbits can occasionally elevate routine acute phase response clinical pathology parameters, including C-reactive protein and creatine kinase, and exacerbate the frequency and severity of myocardial inflammatory cell infiltrates. These effects are similar to that seen in with handling and study-related procedures such as blood collection and intramuscular injection in female NZW rabbits and included elevated stress biomarkers (norepinephrine, epinephrine, cortisol, and corticosterone) and cardiac troponin I.…”
Section: Systemic In-life Parametersmentioning
confidence: 99%